Analisis Alat Kohesi Gramatikal dan Alat Kohesi Leksikal dalam Teks Cerita Pendek Siswa - Alma Patriani Rohiyana (Universitas Indraprasta PGRI, 2021)
This study aims to describe the use of the types of grammatical cohesion tools and lexical cohesion tools in the short story texts of Bogor City Senior High School students, and to determine the most dominant use of cohesion tools. The method used is a qualitative descriptive method. The data source of this research is the short story text of the students of class XI SMA Negeri 4 Bogor. The data collection technique used was literature study. Checking the validity of the data using triangulation. The tools of grammatical cohesion that are the focus are references and conjunctions. The tools of lexical cohesion that are the focus are repetition, synonym, antonym, hyponym, collocation, and equivalence. From the results of the analysis found the use of the grammatical cohesion tool for 78 data. Total reference use was 32 findings (41%) and conjunction 46 findings (59%). Furthermore, the use of lexical cohesion tools totaling 140 data. The use of repetitions of 36 findings (26%), synonym 14 findings (10%), antonym 24 findings (17%), hyponym 10 findings (7%), collocation of 24 findings (17%), and equivalence of 32 findings (23%) . It can be concluded that in 25 short stories students found the use of grammatical and lexical cohesion tools, namely, 78 grammatical cohesion tools and 140 lexical cohesion tool data. The most dominant use of grammatical cohesion tools is the use of conjunctions with the findings of 46 quotations (59%) and the most dominant use of lexical cohesion tools, namely the use of repetitions as much as 36 (26%). Keywords: Grammatical Cohesion Tool, Lexical cohesion tool, Short story.